Effects of Addition Chili Ground to The Characteristics of Bekasam from Cork Fish (Channa striata) During Fermentation - Normayanti Normayanti; Dewi Kartika Sari; Rita Khairina (Universitas PGRI Semarang, 2020)
Bekasam is a fermented fish product made from fish, salt, and roasted rice or rice that is mixed and fermented for 7 days. This study aims to determine the effect of the addition of ground chili at different concentrations on total acid, pH value, total lactic acid bacteria, and sensory properties of cork fish bekasam. The research design used was completely randomized design, 3 treatments and 3 replications. The treatments given were IBG without the addition of ground chili, IBGC1 adding 10% ground chili and IBGC2 adding 20% ground chili. Data were collected for total acid, pH, and total lactic acid bacteria fermentation days 1, 3, 5, and 7. The sensory properties were observed on days 1 and 7. The results showed that the addition of ground chili can reduce pH during 7 days fermentation, but the increase in total acid was not significant. The addition of 10% ground chili has a positive effect on the growth of lactic acid bacteria. The addition of 20% ground chili showed an inhibition of the growth of lactic acid bacteria during fermentation. Sensory test results stated that panelists preferred bekasam with the addition of 10% ground chili compared to control brakes and the addition of 20% ground chili.